Women-led humanitarian architecture in disaster-prone environments: Learning from the Marielle Franco Community-Design Award. (1st June 2021) - Martins, A. Nuno; Hobeica, Liliane; Hobeica, Adib
Abstract: This paper focuses on humanitarian-architecture practices in hazard-prone environments. It highlights women's role in slum-upgrading, aided-self-help, incremental-housing and disaster-risk-reduction processes. We present the experiences of the seven shortlisted nominees to the first edition of the Marielle Franco Community-Design Award, which sought to acknowledge the long-lasting activities of professionals working within vulnerable communities. Although the award did not have a gender focus, all the shortlisted nominees were eventually either women architects or women-led architecture offices, mostly engaged with local NGOs assisting dwellers of fragile settlements while building their capacities. We sought to explore the distinctive features of their practices and how these contribute to improve communities' living conditions. Our research relied on a literature review and the comparative analysis of the profile, practice and achievements of the shortlisted nominees. Our study shows that the processes set forth by these professionals are as important as their architectural results. Furthermore, the outcomes of their work extrapolate the physical dimension to embrace long-term social impacts. By following an empathic and immersive approach in their relationship with the concerned people (in particular women), these female architects could plan, design and build in a truly collaborative mode.